PENJAMINAN KREDIT USAHA KECIL MELALUI GIRALISASI DAN TRANSMISI JAMINAN KEBENDAAN MENJADI TUNAI - Tarsisius Muwarji (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2013)
‘Giralisasi’ is the transformation of a physical guarantee (fixed asset) into cash guarantee. Through a pledge/collateral agreement, assets are given by the owner to an issuing bank. The asset is then givena cash value. The cash value is put into an account and transferred to another bank through SocietyWorldwide Interbank Financial Telecommunication (SWIFT) to guarantee credit for small to mediumscale enterprises. This process and the transformation of guarantees may become an alternative solutionto credit issues faced by small to medium scale enterprises when applying for bank loans. Giralisasi merupakan transformasi jaminan benda menjadi jaminan tunai. Dengan perjanjian gadai, aset diserahkan pemilik kepada bank penerbit, dinilai dengan uang, dimasukkan kedalam rekening dan ditransmisikan ke bank lain melalui Society Worldwide Interbank FinancialTelecommunication (SWIFT) untuk menjamin kredit UKM. Giralisasi dan transformasi jaminanini dapat menjadi alternatif solusi permasalahan jaminan bagi UKM memperoleh kredit bank.